2018
DOI: 10.1021/acs.jafc.8b04682
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Extraction of Pesticides and Polycyclic Aromatic Hydrocarbons in Brazilian Cachaça Using a Modified QuEChERS Method Followed by Gas Chromatography Coupled to Tandem Mass Spectrometry Quantification

Abstract: A modified QuEChERS method was optimized for simultaneous extraction of 93 pesticides and 6 polycyclic aromatic hydrocarbons (PAHs) in cachaça. The procedure employed 20 mL of sample, 10 mL of dichloromethane, 1 g of NaCl, and 6 g of MgSO4. The methods were validated in accordance with pesticide tolerances set by the National Health Surveillance Agency of Brazil and government guidelines of Brazil and the European Union. The linearity of all curves was adequate, with calculated t r higher than the critical va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
(35 reference statements)
2
8
0
2
Order By: Relevance
“…The LOD and LOQ of all analytes are listed in Table S3 in Supplemental Materials. It should be noted that the developed LOD and LOQ of the method were also comparable with recent publications [4145].…”
Section: Resultssupporting
confidence: 86%
“…The LOD and LOQ of all analytes are listed in Table S3 in Supplemental Materials. It should be noted that the developed LOD and LOQ of the method were also comparable with recent publications [4145].…”
Section: Resultssupporting
confidence: 86%
“…A new class of PAHs derivatives, known as chlorinated PAHs (Cl-PAHs), have been attracting increasing interest. Emerging Cl-PAHs are also ubiquitous and hazardous pollutants akin to PAHs and other halogenated aromatic compounds, such as polychlorinated dibenzo-p-dioxins, dibenzofurans, and PCBs; the QuEChERS method has been used for sample preparation [120].…”
Section: Process Contaminantsmentioning
confidence: 99%
“…Recently, many studies have shown use of gas or liquid chromatography in combination with mass spectrometry such as gas chromatography in combination with electron impact ionization mass spectrometry (GC-EI-MS) [9,10,13], gas chromatography in combination with electron impact ionization tandem mass spectrometry (GC-EI-MS/MS) [14][15][16], liquid chromatography-atmospheric pressure photon ionization tandem mass spectrometry (LC-APPI-MS/MS) [17][18][19], liquid chromatography-fluorescent detector in serial with tandem mass spectrometry (LC-FLD-MS/MS) [20] for analysis of PAHs and their derivative compounds such as nitro-PAHs and hydroxyl-PAHs in both environmental and food sample matrices. Among these methods, GC-EI-MS/MS with excellent selectivity, high sensitivity, and robustness has been a modern and effective method for PAHs analysis in several laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, GC-EI-MS/MS with excellent selectivity, high sensitivity, and robustness has been a modern and effective method for PAHs analysis in several laboratories. In addition, several sample preparation techniques such as ultrasonic-assisted liquid extraction [2,11,15], traditional Soxhlet extraction, solid phase extraction (SPE) [16,21], pressured solvent extraction (or accelerated solvent extraction, ASE) [10,13], and QuEChERS [9,16,17] have been developed for extraction of PAHs in the real sample matrices prior analysis by gas/liquid chromatography. However, ultrasonic-assisted extraction (UAE) method was considerably used as a green extraction method because of low toxic solvent consumption, high extraction efficiency, and less extraction time, especially for particulate matter or solid samples [22][23][24].…”
Section: Introductionmentioning
confidence: 99%